Genotyping‐by‐Sequencing. Issue 1 (3rd March 2017) - Wallace, Jason G.; Mitchell, Sharon E.
Abstract: Genotyping‐by‐sequencing (GBS) refers to a suite of related methods that obtain genotype data from samples by using restriction enzyme digestion followed by high‐throughput sequencing. GBS is a refinement of restriction site–associated DNA sequencing (RADseq) methods, with a goal of being able to perform library preparations quickly, cost‐effectively, and in a high‐throughput manner. This protocol contains the steps necessary to go from purified DNA to Illumina‐ready libraries. It also covers the considerations that go into planning a GBS experiment. © 2017 by John Wiley & Sons, Inc.